228k views
5 votes
Can someone please explain this for me I’m
Not sure of the steps. See photo above

Can someone please explain this for me I’m Not sure of the steps. See photo above-example-1

2 Answers

7 votes


\bf \cfrac{x^8}{x^(14)}\implies x^8x^(-14)\implies x^(8-14)\implies x^(-6)\implies \stackrel{\textit{using the power rule}}{-6x^(-7)\implies \cfrac{-6}{x^7}}

User Madcrazydrumma
by
5.4k points
2 votes

Question 1:

We have the following expression:


4x ^ {-4}

By definition of power properties we have to:


a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}

Then, rewriting the expression:


\frac {4} {x ^ 4}

ANswer:


\frac {4} {x ^ 4}

Question 2:

For this case we have the following expression:


\frac {x ^ 8} {x ^ {14}} =

By definition of power properties of the same base we have:


x ^ n * x ^ m = x ^ {n + m}

Then, we can rewrite the denominator of the expression as:


\frac {x ^ 8} {x ^ 8 * x ^ 6} =

Simplifying terms of the numerator and denominator:


\frac {1} {x ^ 6}

ANswer:


\frac {1} {x ^ 6}

User Ginger Opariti
by
5.5k points